KONSEP KETATANEGARAAN DALAM ISLAM - Herawati, Andi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
Qur'an as scripture has laid the principles and ethical values ​​in society and state. The principles practiced by the Prophet in his capacity as head of state, so he was able to create a system of government that is peaceful, prosperous and democratic. Government that upholds justice, equality, and protection of human rights